Vibration on the backs of mistblower operators: is it only a (dis)comfort question?. (September 2019) - Calvo, Angela; Preti, Christian; Cutini, Maurizio; Deboli, Roberto
Abstract : Mistblowers, also called powered backpack or knapsack sprayers, are found in many countries. Because of their low cost, adaptability and easy to use, they are often used in small-scale farms and in sloping fields. They are usually powered by an internal combustion engine which produces vibrations that are transmitted to the operator's body (hands, back, shoulders). In this work the vibration produced on the backs of twenty operators operating three mistblowers were studied in field, with the tank filled with 1, 5 and 10 l of pesticide with low and high engine speeds. The former occurs when the operator moves in field, the latter during the spraying. The vibration behaviour of the mistblowers was also tested in laboratory. There are no suitable standards to determine the risk of the vibration exposure to the operator's back using backpack machines. The standard ISO 2631-1:1997 allows only a discomfort condition to be estimated. In our tests the highest Comfort Vibration Total Values (CVTV) were observed in field with the tank filled with 1 l of pesticide and at low engine speed. There were no statistically significant differences in the CVTVs among the operators, and one of the three machines (the oldest with a low level of maintenance) produced the highest CVTVs; up to 0.62 m s −2 . The x -axis (fore-and-aft direction) was the most dominant. The dominant one-third octave band centre frequency (or mid-frequency, ISO 5349-1: 2001) was 40 for the low engine speed and 100 Hz for the high engine speed. Highlights: Vibration on operators' back produced by mistblowers. Misblowers vibration analysis in field and in laboratory. Use of 2631-1 standard to evaluate the comfort vibration total values (CVTVs). Highest vibration values when the mistblower tank is almost empty. Highest discomfort if the mistblower is not properly maintained.